PAUCITY AND MULTIPLICITY IN THE GLORIOUS QURAN: A MORPHOPRAGMATIC ANALYSIS - Abdurrahman, Israa Burhanuddin; Ibrahim, Amina Khalid; Hazem, Ali Hussein (Universitas Islam Negeri Ar-Raniry, 2022)
In this study, a morpho-pragmatic analysis of broken plural in the Glorious Quran is tackled to answer the question whether the types of broken plural can be replaced without affecting the meaning, and to achieve the aim that these various forms are utilized thoughtfully and creatively and are never used randomly. Accordingly, it is hypothesized in the present study that the broken plural multi forms in the Glorious Quran are selected sensibly and they function in a way that leads the reader to a scene of wider conceptual view and consideration. The value of this study lies in the endeavor to widen the horizon of the reader that the variety of broken plural forms in the Glorious Quran are much more meaningful than they look. This paves the way to consider many items in the Holly Quran as significant, worthwhile, and telling. To prove the hypothesis and achieve the aim, this paper adopts Dressler and Merlini-Barbaresi’s (1994) model in analyzing the chosen excerpts where language choices can be conceived at the level of pragmatics in relation to morphology. Eight Quranic texts are selected, analyzed, discussed, and conclusions are finally derived to assert that the various forms of broken plural in the Glorious Quran are manipulated exquisitely in an effective way.